Analisis Materi Islam Wasathiyah pada Mata Pelajaran Aqidah Akhlak di Madrasah Aliyah - Siti Rohmah; Zakiyatul Badriyah (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
The Islamic concept of wasathiyah is taken from the meaning of the Quranic verse surah Al-Baqarah verse 143. Wasathiyah Islam is the idea of moderation in religion. Religious moderation is taken from the perspective of the Qur'an with several references to interpretation. It can be concluded that religious moderation in its implications is in accordance with the teachings of the Guidelines of Muslims, namely the Qur'an.